Comparison of photographic and visual assessment of occlusal caries with histology as the reference standard - Boye Uriana; Walsh Tanya; Pretty Iain A; Tickle Martin (BMC, 2012)
Abstract Background The purpose of this study was to compare diagnostic performance for the detection of caries using photographs with an established visual examination method and histological sections as the reference standard. Methods 50 extracted permanent teeth were assessed for the presence of occlusal caries by 9 examiners using two methods; traditional visual examination developed by BASCD and photographs produced by an intra-oral camera. For both methods, diagnoses were made at "caries into dentine" level. The teeth were histologically sectioned and the diagnostic decisions using visual and photographic assessment were compared to the histological reference standard. Inter- and intra- examiner reliability for the methods was assessed and weighted kappa values were calculated. Results The visual examination method had a median sensitivity value of 65.6% and a median specificity value of 82.4%. The photographic assessments method had a median sensitivity of 81.3% and a median specificity of 82.4%. Conclusions The photographic assessments method had a higher sensitivity for caries detection than the visual examination. The two methods had comparable specificities and good intra- and inter- examiner reliability.